Narrative about the LGBTQ+ Community in Nasz Dziennik - Ludwicka, Aleksandra (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume III, 2025)
The aim of the article is to present how Nasz Dziennik portrays members of the LGBTQ+ community. The paper seeks to demonstrate the linguistic strategies of manipulation used by the authors of the articles to depict non-heteronormative individuals. The narrative is conducted according to the authors’ own worldview, in a non-objective manner. Scientific facts are subjected to ideological interpretations dictated by personal conservative beliefs. The research material consists of selected excerpts from articles published in Nasz Dziennik in 2023.